2014
DOI: 10.1016/j.vaccine.2014.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends in circulating rotavirus strains in Pune, western India in 2009–2012: Emergence of a rare G9P[4] rotavirus strain

Abstract: The study highlights the huge burden of rotavirus disease and changing profile of circulating rotavirus strains displaying emergence of G9P[4] reassortant strains in Pune, western India and emphasizes the need to analyze the entire genomic constellation of rotavirus strains for better evaluation of the impact of rotavirus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 13 publications
4
14
1
Order By: Relevance
“…Surveillance study carried out on rotaviruses during the years 2009‐2012 in Pune, western India showed G1P[8] (31.4%), G2P[4] (20.2%), and G9P[8] (11.8%) strains were the most common types in circulation. Also the study indicated that the prevalence of G9P[8] RVA strains were found to be increased during the year 2009 (15.3%) and as the second highest (27.0%) in the subsequent year 2010 . Sequencing of all the G9 RV strains of the study showed clustering in lineage III (data unpublished).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Surveillance study carried out on rotaviruses during the years 2009‐2012 in Pune, western India showed G1P[8] (31.4%), G2P[4] (20.2%), and G9P[8] (11.8%) strains were the most common types in circulation. Also the study indicated that the prevalence of G9P[8] RVA strains were found to be increased during the year 2009 (15.3%) and as the second highest (27.0%) in the subsequent year 2010 . Sequencing of all the G9 RV strains of the study showed clustering in lineage III (data unpublished).…”
Section: Introductionmentioning
confidence: 76%
“…Recent studies have documented proportion of RVA infections with G9 strains at 13‐40% level in acute gastroenteritis . Increase in the circulation of G9P[8] RV strains has also been reported during the study period from western and northern India . Surveillance study carried out on rotaviruses during the years 2009‐2012 in Pune, western India showed G1P[8] (31.4%), G2P[4] (20.2%), and G9P[8] (11.8%) strains were the most common types in circulation.…”
Section: Introductionmentioning
confidence: 98%
“…Of these, G1P[8] alone is responsible for a majority (37.7%) of rotavirus infections . Surveillance studies conducted across India have shown a bulk of rotavirus disease attributable to G1P[8] strains for several years …”
Section: Introductionmentioning
confidence: 99%
“…In India, data on complete genomes of G1P[8] strains is limited to three strains isolated from children who suffered from acute gastroenteritis . In studies conducted recently for surveillance of rotavirus diarrheal disease and strains among children from Pune, western India, history of rotavirus vaccination with either of the monovalent or pentavalent vaccines was noted in 10% of the children hospitalized for acute gastroenteritis . Rotavirus positivity was significantly higher (47%) in non‐recipients than in recipients (28.3%) of vaccine .…”
Section: Introductionmentioning
confidence: 99%
“…Given the predominant RVA genotype strains, the rare genotype G9P[4], which has been detected worldwide since the 1990 s, is likely a reassortant between two common genotype strains [Matthijnssens et al, ]. However, despite its infrequent appearance in the past decade, recent reports have shown that G9P[4] is being detected more often [Afrad et al, ; Quaye et al, ; Reesu et al, ; Chitambar et al, ]. Particularly, G9P[4] detection increased in Latin American countries, accounting for 80%, 66%, and 36% of detected RVA in Mexico, Guatemala, and Honduras, respectively, during 2009–2010 [Quaye et al, ].…”
Section: Introductionmentioning
confidence: 99%